Insulin Resistance Adversely Affect IVF Outcomes in Lean Women Without PCOS - Wang, Haoyu; Zhang, Yu; Fang, Xuhui; Kwak-Kim, Joanne; Wu, Li (Frontiers in Endocrinology, 2021)
Objective To investigate the effects of insulin resistance (IR) on IVF outcomes and a potential underlying mechanism in lean women without PCOS. Design A prospective cohort study at the University Clinic. Setting IVF center at the University setting. Patients A total of 155 lean women (body mass index <25) without PCOS undergoing IVF cycle. Intervention Patients were allocated to IR and non-IR groups based on HOMA-M120. Main Outcome Measure(s) IVF outcomes, including egg quality, the percentage of mature oocytes, fertilization rate, blastocyst formation rate, advanced embryo rate, and cumulative live birth rate were investigated. Auto-immune parameters, peripheral blood immunophenotypes, thyroid hormone, homocysteine, and 25-OH-vitamin D3 (25-OH-VD3) levels were analyzed. Results The percentage of mature oocytes and blastocyst formation rate were significantly lower in the IR group as compared with those of the non-IR group (p<0.05, respectively). The proportion of peripheral blood CD19+ B cells was significantly higher in the IR group than those of the non-IR group (p<0.05). Homocysteine, 25-OH-VD3, and auto-immune parameters were the same between the two groups. Conclusion In lean infertile women without PCOS, IR is associated with the decreased percentage of mature eggs and poor embryo quality in which B cell immunity may play a role.